Implementasi Kepuasan Kerja Berbasis Kompetensi, Komunikasi, Dan Kompensasi Untuk Meningkatkan Kinerja Guru: Studi Kasus Pada Smkn 1 Miri Sragen - Ervin Yoga Pratama; Siti Fatonah (STIE AUB Surakarta, 2025)
The aim of this research is to examine the influence of competence, communication and compensation on job satisfaction and teacher performance at SMKN 1 Miri Sragen. The research method used is a quantitative method. The population in this study was 100 teachers and the sample was 80 teachers. The research object is job satisfaction and teacher performance. All variables are measured using a Likert scale. The type of data used is primary data. The analytical tool used is multiple linear regression. The determination results show a total R2 value of 0.594, meaning that teacher performance is explained by Competence, Communication, Compensation and Job Satisfaction at 59.4% and the remaining 40.6% is explained by other variables outside the research model. The results of multiple regression analysis show that simultaneously (F Test) it is concluded that the variables of competence, communication, compensation and job satisfaction have an significant influence on teacher performance. The results of the path analysis prove that the direct path or direct influence of competence on teacher performance in the SMK Negeri 1 Miri Sragen Regency is the most dominant and effective path among other variables and influences, because it has a positive and significant effect in improving teacher performance by a significant 0.375. Then job satisfaction has an significant effect on teacher performance with a significant coefficient of 0.225. The mediating role of job satisfaction in the analysis of this research model is able to mediate communication and compensation, but is not able to mediate competence on teacher performance in the SMK Negeri 1 Miri Sragen Regency environment.